NILAI KEARIFAN LOKAL DALAM TRADISI MENYUMBUN DAN RELEVANSINYA DENGAN PEMBELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Difa Angraini; Syahrial; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the local wisdom values contained in the menyumbun tradition and its relevance to Integrated Science and Social Studies (IPAS) learning in Grade IV of elementary school. This research employed a qualitative descriptive method with a case study approach. Data were collected through interviews with community leaders and elementary school teachers, observations, and documentation. The results indicate that the menyumbun tradition contains ecological, social, educational, and spiritual values. Ecological values are reflected in environmental conservation practices and sustainable resource use. Social values are shown through cooperation and solidarity among community members. Educational values appear in the intergenerational transmission of knowledge through experiential learning. Spiritual values are demonstrated in gratitude and religious awareness in utilizing natural resources. Furthermore, the tradition aligns with IPAS learning objectives in Phase B of the Merdeka Curriculum, particularly in ecosystem concepts, natural resource utilization, environmental conservation, and social interaction. Therefore, the menyumbun tradition has strong potential as a contextual and local wisdom-based learning resource in elementary education.